On the Use of Potential Denaturing Agents for Ethanol in Direct Ethanol Fuel Cells - Domnik Bayer; Florina Jung; Birgit Kintzel; Martin Joos; Carsten Cremers; Dierk Martin; Jörg Bernard; Jens Tübke (International Journal of Electrochemistry)
Acidic or alkaline direct ethanol fuel cells (DEFCs) can be a sustainable alternative for power generation if they are fuelled with bio-ethanol. However, in order to keep the fuel cheap, ethanol has to be exempted from tax on spirits by denaturing. In this investigation the potential denaturing agents fusel oil, tert-butyl ethyl ether, and Bitrex were tested with regard to their compatibility with fuel cells. Experiments were carried out both in sulphuric acid and potassium hydroxide solution. Beside, basic electrochemical tests, differential electrochemical mass spectrometry (DEMS) and fuel cell tests were conducted. It was found that fusel oil is not suitable as denaturing agent for DEFC. However, tert-butyl ethyl ether does not seem to hinder the ethanol conversion as much. Finally, a mixture of tert-butyl ethyl ether and Bitrex can be proposed as promising candidate as denaturing agent for use in acidic and alkaline DEFC.